History of bluetongue research at Onderstepoort - Verwoerd, D W (Onderstepoort journal of veterinary research, 2009)
Research on this economically important disease of ruminants, especially sheep, which had been named bluetongue by farmers in the 19th century, has been part and parcel of the activities at Onderstepoort ever since its establishment in 1908 and therefore covers a full century of the OVI's existence. In view of Onderstepoort's centenary celebration a brief overview of this research is given in terms of the historic milestones which influenced and guided global research on this and other viral diseases of animals.